Effects of Gadolinium-based magnetic resonance imaging contrast media on red blood cells and K562 cancer cells - Benjamaporn Supawat (2020)
© 2020 The Author(s) Background: Gadolinium-based contrast media (GBCM) are commonly used in diagnostic magnetic resonance imaging (MRI) in clinical applications. The objective of this study is to evaluate the antioxidant properties and effects on red blood cells (RBCs) and K562 cancer cells of three GBCMs (i.e.; gadoterate meglumine, gadopentetate dimeglumine, and gadobenate dimeglumine) inin vitro levels. Methods: For determiningin vitro antioxidant properties, the di (phenyl)-(2,4,6-trinitrophenyl) iminoazanium (DPPH) and ferric reducing ability of plasma (FRAP) assay were used. For determining effect on red blood cells, hemolysis, morphology and reactive oxygen species (ROS) were used. For determining effect on K562 cancer cells, cytotoxicity and ROS were used. The GBCM -exposed cells were compared to corresponding non-exposed control groups at various harvest times. Results: The results show no changes occurring in the DPPH data. However, there were significant increases based on FRAP data in three GBCMs compared to the corresponding control at all concentrations. The ROS, morphology, and percentage of hemolysis in red blood cells indicated that no change had occurred in three GBCMs-exposed red blood cells compared to the corresponding non-exposed control groups at all harvest times. The percentage of cell viability in K562 cancer cells showed decreases in gadoterate meglumine- and gadobenate dimeglumine- in a concentration dependent manner, but did not show same in gadopentetate dimeglumine-exposed K562 cancer cells. The percentage of ROS in K562 cancer cells indicated that no change in three GBCMs-exposed cells had occurred when compared to the corresponding non-exposed control groups at all harvest times. Conclusion: These findings suggests thatin vitro antioxidant properties exhibited by those three GBCMs depends on their concentration and species of radical in testing assay. There were no toxic effects from those GBCMs when red blood cells were exposed in an in vitro condition. In addition, some of those GBCMs could induce cell death in cancer cells.